SAT0193 Early discontinuation of first line biological treatment with etanercept in patients with rheumatoid arthritis: results from the italian gisea registry. (12th June 2018) - Sebastiani, M.; Manfredi, A.; ,; Iannone, F.; Gremese, E.; Bortoluzzi, A.; Favalli, E. G.; Gorla, R.; Salaffi, F.; Fusaro, E.; Foti, R.; Cantarini, L.; et al.
Abstract : Background: Tumor necrosis factor-α inhibitors (TNFi) are usually the first biologic drugs employed in rheumatoid arthritis (RA) after failure of conventional disease-modifying antirheumatic drugs (DMARDs). Retention rate is a useful surrogate marker of effectiveness and safety in real life, but few studies investigated the causes of early discontinuation of these drugs. Objectives: Aim of the study was to investigate the possible predictors of early discontinuation (within 1 year of treatment) of etanercept (ETA) in RA patients enrolled into the GISEA (Italian Group for the Study of Early Arthritis) registry. Methods: RA patients who began etanercept as first biologic DMARD were included in the study. For all patients age, sex, disease duration, smoking status, the intake of glucocorticoids and DMARD, clinical and serological data, comorbidities and extra-articular manifestations were collected. Results: We analyzed 477 RA patients (females/males 382/95, mean age 51.3±14.1 years; mean DAS28 5.4±1.5); rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA) were positive in 66% and 62.3%, respectively. Comorbidities were observed in 16.6% of patients, mainly cardiovascular diseases, while extra-articular RA manifestations were recorded in 6.3%. Concurrent DMARDs therapies were reported in 54.3% of patients, mainly methotrexate (40.5%), while 52.4% of subjects taken low doses of steroids. Seventy patients (14.7%) discontinued ETA during the first year (for inefficacy in 43 patients, adverse events in 22, and other reasons in 5). The presence of comorbidities and a combination therapy with DMARDs different by MTX were independent predictors of early discontinuation of ETA at multivariate analysis (see table 1). The association with MTX didn't increase the 1-year retention rate of ETA. No significant associations were observed with steroids, presence of RF or ACPA or the disease activity at baseline. Conclusions: ETA demonstrated a high persistence in RA patients and after 12 months more than 85% of patients continued the treatment. The presence of comorbidities and a combination therapy with DMARDs different by MTX were associated to an early withdrawal of the drug. Disclosure of Interest: None declared